(untitled) (UNIZIK Journal of Marketing, 2026)
This study investigated the relationship between vendor-managed inventory and procurement performance of upstream oil and gas companies in South-South, Nigeria. The independent variable was vendor-managed inventory, while material availability, timeliness, and cost reduction served as measures of the dependent variable (procurement performance). The study population comprised twenty-four (24) upstream oil and gas companies in South-South Nigeria as enlisted in the finelib.com Nigerian Directory and Search Engine. A census method was adopted in selecting the sample size, administering three copies of a structured questionnaire to Operations Managers, Procurement/Logistics Managers, and Marketing Managers from each of the 24 companies, yielding 72 respondents. Data were analyzed using Pearson’s Product Moment Correlation and Linear Regression Analysis with the aid of Statistical Package for Social Sciences (SPSS) version 23.0. The analysis revealed statistically positive and significant relationships between vendor managed inventory and all measures of procurement performance. Specifically, vendor-managed inventory showed a moderate positive relationship with material availability (r = 0.440, p < 0.05), a strong positive relationship with timeliness (r = 0.603, p < 0.05), and a moderate positive relationship with cost reduction (r = 0.471, p < 0.05). Regression analysis further confirmed that vendor-managed inventory significantly predicts procurement performance (R² = 0.412, F = 23.456, p < 0.05). The study concluded that vendor-managed inventory significantly relates to procurement performance of upstream oil and gas companies in South-South, Nigeria. It was recommended that managers should constantly evaluate current inventory practices to ensure VMI applicability, integrate environmental protection considerations, and adopt advanced demand forecasting techniques to improve material availability and timely delivery.